Estimation of modern state of agroindustrial complex of Vinnytsia region - Moroz, O. O.; Semtsov, V. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The estimation of basic socio-economic indexes which characterize the modern state of agribusiness industry of Vinnytsia region and its agrarian society is carried out in the article. The problem aspects of development of industry are defined, taking into account market reforms. Negative influence of shadow economy on the development of agrarian sector of economy is considered.